Characterization of Al-Cu-Graphite nanocomposite prepared by powder metallurgy and mechanical alloying - Azizan, Nur Shamilatul Akhma binti (2020)
Al-Cu composite has good mechanical properties and corrosion resistance but lower toughness and ductility which limits them at high temperature application. Al-Cu could reinforced with graphite (C) to overcome the problem by producing Al(C) or Cu(C) solid solutions. In this study, the effect of milling time on structural and microstructural of Al- Cu-graphite nanocomposite at different composition prepared by powder metallurgy and mechanical alloying was studied. Elemental powder of aluminium (Al), copper (Cu) and graphite (C) were milled in a planetary ball mill using 5 mm of zirconia ball at 2, 4, 6 and 8 h. Then, the nanocomposites powder were compacted using cold compaction of 400 MPa. These nanocomposites were characterized for its structural properties, microstructural and green density. Increasing milling time up to 8 h of milling only produced structural changes in nanocomposites but not enough to produce a solid solution. Rapid refinement was induced in higher graphite content composite. Increasing milling time up to 8 h and higher graphite content produced small Al-Cu-graphite particles which contribute to denser composite.